2004
DOI: 10.1021/ma048701u
|View full text |Cite
|
Sign up to set email alerts
|

Counteranion-Controlled Properties of Polyelectrolyte Multilayers

Abstract: Polyelectrolyte multilayers consisting of poly(diallyldimethylammonium chloride) (PDADMA) and poly(sodium 4-styrenesulfonate) (PSS) were studied on a quartz crystal microbalance (QCM) utilizing a novel method to determine the elastic properties of the films. Since the multilayer was found to consist of a hard core and soft outer layer, as can be realized on the basis of the multilayer zone model, the multilayer films were made thick enough to reveal the elastic properties of the bulk material of the film. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(186 citation statements)
references
References 36 publications
10
174
2
Order By: Relevance
“…Ions from the Hofmeister series, a classification of ions going from cosmotropic (water structure making, highly hydrated ions) to chaotropic (water structure disrupting, weakly hydrated ions), were used in several studies to assess the importance of the ion type. It was found that thickness, [49] stiffness, [50] and swelling behavior [51] could all be modified by changing ion type.…”
Section: Charge Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ions from the Hofmeister series, a classification of ions going from cosmotropic (water structure making, highly hydrated ions) to chaotropic (water structure disrupting, weakly hydrated ions), were used in several studies to assess the importance of the ion type. It was found that thickness, [49] stiffness, [50] and swelling behavior [51] could all be modified by changing ion type.…”
Section: Charge Matchingmentioning
confidence: 99%
“…[98,99] Several other methods, relying on different physical principles, are well suited to characterizing thin films, some of them in a liquid state. These include quartz crystal microbalance, [50,100] piezo-rheometry, [101] resonance frequency, [102] bulging tests, [103] the pendant drop technique, [104] osmotic pressure, [105] or the capillary wave technique [106] in the case of free-standing films. The stiffness of PEM can be modulated from a few kPa to several GPa depending on the structural properties of the polyelectrolytes, but also on the degree of cross-linking inside the film.…”
Section: Modulation Of Mechanical Propertiesmentioning
confidence: 99%
“…This picture has changed over the past few years as several innovative mechanical testing methods, such as the quartz crystal microbalance [23], capillary wave techniques [24] ], PEMUs showed aspects reminiscent of both rubber-like and glass-like materials, with a broad elastic modulus ranging from 0.00001 to 12 Gpa [29,30].…”
Section: Mechanical Properties Of Polyelectrolyte Multilayersmentioning
confidence: 99%
“…[8][9][10][11][12][13] Because the degree of charge dissociation in polyelectrolytes is dependent on the types of ion-pairs, the physical properties of polyelectrolyte hydrogels such as conductivity, elasticity and swelling ratio are affected by counterions as well as external stimuli. [14][15][16][17] Recently, there have been increasing research efforts of combining hydrogels with other functional materials to extend their potential applications. For example, the photonic crystals comprising hydrogels exhibit unique tunable photonic band gaps in response to the various stimuli including temperature, pH, ionic strength, solvent compositions and electric fi eld.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%